Multimodal learning for quality of experience in video-to-retail applications: algorithms and deployment - Zhang, Huaizheng (Nanyang Technological University, 2022)
Multimedia content has dominated the Internet, fueled by an unprecedented number of multimedia applications. Among them, a kind of emerging application, termed Video-to-Retail (V2R), has attracted attention as it can seamlessly integrate both online video and online retail and provide users with enhanced Quality of Experience (QoE) to enjoy both. This dissertation takes V2R as an example to dive into the following requirement that widely exists in many multimedia applications: maintaining QoE to increase application providers' revenue while building an efficient backend system to save expenditure.